Maud's line ebook A novel. - Verble, Margaret (2024)
A finalist for the Pulitzer Prize and "a gorgeous window onto the Cherokee world in Oklahoma, 1928 . . . utterly authentic, tender and funny, vivid and smart" (Roxana Robinson, author of Sparta ). Eighteen-year-old Maud Nail lives with her rogue father and sensitive brother on one of the allotments parceled out by the US Government to the Cherokees when their land was confiscated for Oklahoma's statehood. Maud's days are filled with hard work and simple pleasures, but often marked by violence and tragedy, a fact that she accepts with determined practicality. Her prospects for a better life are slim, but when a newcomer with good looks and books rides down her section line, she takes notice. Soon she finds herself facing a series of high-stakes decisions that will determine her future and those of her loved ones. Maud's Line  is an accessible, sensuous, and vivid chronicle of the American West and its people. "An absolutely wonderful novel. . . . Margaret Verble can drop you from great heights and still easily pick you up. I will read anything she writes, with enthusiasm." —Jim Harrison, New York Times– bestselling author of  Legends of the Fall "Writing as though Daniel Woodrell nods over one shoulder and the spirit of Willa Cather over the other, Margaret Verble gives us Maud, a gun-toting, book-loving, dream-chasing young woman whose often agonizing dilemmas can only be countered by sheer strength of heart." —Malcolm Brooks, author of  Painted Horses "A compelling story peopled with flawed yet sympathetic characters, sharing insights into Cherokee society on the parcels of land allotted to them after the Trail of Tears." — Kirkus Reviews